The Unequal Pandemic COVID- 19 and Health Inequalities - Bambra, Clare (Policy Press, 2021)
EPDF and EPUB available Open Access under CC-BY-NC- ND It has been claimed that we are 'all in it together' and that the COVID-19 virus 'does not discriminate'. This accessible, yet authoritative book dispels this myth of COVID-19 as an 'equal opportunity' disease, by showing how the pandemic is a syndemic of disease and inequality. Drawing on international data and accounts, it argues that the pandemic is unequal in three ways: it has killed unequally, been experienced unequally and will impoverish unequally. These inequalities are a political choice: with governments effectively choosing who lives and who dies, we need to learn from COVID-19 quickly to prevent growing inequality and to reduce health inequalities in the future. COVID-19 is an unequal pandemic.